IMPLICATION OF GLOBAL WARMING TO HEALTH SECURITY - FIDELIS, M.N (NIGERIAN JOURNAL OF HEALTH PROMOTION, 2023)
The term health security is used to depict health issues that have significant influence on human security. To secure the health of the public, factors that pose threat to human health must be addressed. Such factors include global warming and environmental changes. This paper discussed the causes of global warming, the implication of global warming, steps to be adopted in reducing the implication of global warming. The paper recommends among others that human activities that cause global warming should be checkmated through enactment and implementation of law and policy formulation, awareness on the need to ensure health security by acting on climate change should be created, empirical studies should be carried out on health protection from global warming.